Uncoupling Lipid Metabolism from Inflammation through Fatty Acid Binding Protein-Dependent Expression of UCP2 - Xu, Hongliang (Mol Cell Biol, 2015)
Chronic inflammation in obese adipose tissue is linked to endoplasmic reticulum (ER) stress and systemic insulin resistance. Targeted deletion of the murine fatty acid binding protein (FABP4/aP2) uncouples obesity from inflammation although the mechanism underlying this finding has remained enigmatic. Here, we show that inhibition or deletion of FABP4/aP2 in macrophages results in increased intracellular free fatty acids (FFAs) and elevated expression of uncoupling protein 2 (UCP2) without concomitant increases in UCP1 or UCP3. Silencing of UCP2 mRNA in FABP4/aP2-deficient macrophages negated the protective effect of FABP loss and increased ER stress in response to palmitate or lipopolysaccharide (LPS). Pharmacologic inhibition of FABP4/aP2 with the FABP inhibitor HTS01037 also upregulated UCP2 and reduced expression of BiP, CHOP, and XBP-1s. Expression of native FABP4/aP2 (but not the non-fatty acid binding mutant R126Q) into FABP4/aP2 null cells reduced UCP2 expression, suggesting that the FABP-FFA equilibrium controls UCP2 expression. FABP4/aP2-deficient macrophages are resistant to LPS-induced mitochondrial dysfunction and exhibit decreased mitochondrial protein carbonylation and UCP2-dependent reduction in intracellular reactive oxygen species. These data demonstrate that FABP4/aP2 directly regulates intracellular FFA levels and indirectly controls macrophage inflammation and ER stress by regulating the expression of UCP2.